БОШЛАНҒИЧ СИНФЛАРДА ЖИСМОНИЙ МАШҒУЛОТЛАРНИ ТАШКИЛ ҚИЛИШ УСУЛЛАРИ - Турғунов, Б.У.; Исоқов, Ж.З. (SCIENCE and SOCIETY, 2020)
Promoting a healthy lifestyle among primary school children, providing the necessary knowledge to keep the rules of sports activities when organizing lessons in plysical culture.